Sistem Informasi Management Persediaan Barang Menggunakan Metode Moving Average Cost Method - Elin Gusbriana; Heni Sulistiani (PT. Tech Cart Press, 2023)
CV Dwi Putra is one of the chip shops that sells various types of chips with various flavors. However, in managing inventory, they still use manual methods that lead to inaccuracies in stock quantities between reality and records, as well as the lack of computerized systems to manage incoming and outgoing goods. Manual data processing also causes errors in recording final stock, delays in making reports, and makes CV Dwi Putra staff have to calculate and re-record the amount of stock of goods. In addition, the difficulty of determining the updated cost of goods sold is also a problem. The system is built using the Extreme Programming development method, as well as using use case diagram design models, activity diagrams, and class diagrams to illustrate inventory information system models. In its creation, this system uses PHP, HTML, JavaScript, JQuery, and MySQL programming languages, using the Codeigniter Framework. The inventory information system that has been developed has benefits in managing stock data better than the previous system. The system is able to manage incoming goods data (purchases) and outgoing goods data (sales), so as to reduce errors in recording final stock. In addition, the system also helps in making purchase and sales reports easier, faster, and on time. By using the Moving Average Cost method, the system also helps in determining the cost of goods sold when there is an increase or decrease in price.